2021
DOI: 10.1038/s41408-021-00558-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experience of CPX-351 as first-line treatment for patients with acute myeloid leukemia

Abstract: To investigate the efficacy and toxicities of CPX-351 outside a clinical trial, we analyzed 188 patients (median age 65 years, range 26–80) treated for therapy-related acute myeloid leukemia (t-AML, 29%) or AML with myelodysplasia-related changes (AML-MRC, 70%). Eighty-six percent received one, 14% two induction cycles, and 10% received consolidation (representing 22% of patients with CR/CRi) with CPX-351. Following induction, CR/CRi rate was 47% including 64% of patients with available information achieving m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“… 35 In a German retrospective, multicenter analysis in patients with newly diagnosed t-AML or AML-MRC, treatment with CPX-351 resulted in a median OS of 21 months. 36 In all 3 studies, CPX-351 was associated with an acceptable safety profile, consistent with results from the phase 3 trial. However, these studies did not address the issue of HRU.…”
Section: Discussionsupporting
confidence: 72%
“… 35 In a German retrospective, multicenter analysis in patients with newly diagnosed t-AML or AML-MRC, treatment with CPX-351 resulted in a median OS of 21 months. 36 In all 3 studies, CPX-351 was associated with an acceptable safety profile, consistent with results from the phase 3 trial. However, these studies did not address the issue of HRU.…”
Section: Discussionsupporting
confidence: 72%
“…In a phase III trial including 309 patients from 60 to 75 years old with ND high-risk AML, CPX-351 showed a significantly improved median OS and higher ORR compared to the classic 7 + 3 approach, despite a longer time to neutrophil and platelet count recovery [ 160 ]. CPX-351 was approved by the FDA and EMA for ND and therapy-related (TR) AML, and real-world data confirmed the efficacy of CPX-351 in monotherapy, with promising outcomes after HSCT [ 161 ].…”
Section: New Formulations Old Drugsmentioning
confidence: 99%
“…Among those 28 responding patients, 16 (57%) achieved MRD negativity (defined as < 10 −3 ), including 8/14 (57%) patients who had available MRD data and proceeded to HCT; so far, OS among transplanted patients was not significantly different between patients with versus without MRD negativity [ 40 ]. In a German retrospective, multicenter analysis in patients with newly diagnosed therapy-related AML or AML-MRC [ 41 ], a total of 36 patients who achieved CR or CRi underwent MRD analysis (by MFC), and 23/36 (64%) achieved MRD negativity (defined as < 10 −3 ); further, all 23 patients proceeded to HCT and continued to exhibit MRD negativity at the time of HCT [ 41 ]. The achievement of MRD negativity was associated with longer OS overall ( p = 0.01) and among patients who proceeded to HCT ( p = 0.02), but not in a multivariable analysis for OS [ 41 ].…”
Section: Promising Strategies To Achieve Mrd Negativity In High-risk Amlmentioning
confidence: 99%
“…In a German retrospective, multicenter analysis in patients with newly diagnosed therapy-related AML or AML-MRC [ 41 ], a total of 36 patients who achieved CR or CRi underwent MRD analysis (by MFC), and 23/36 (64%) achieved MRD negativity (defined as < 10 −3 ); further, all 23 patients proceeded to HCT and continued to exhibit MRD negativity at the time of HCT [ 41 ]. The achievement of MRD negativity was associated with longer OS overall ( p = 0.01) and among patients who proceeded to HCT ( p = 0.02), but not in a multivariable analysis for OS [ 41 ]. Although these real-world studies found no consistent difference in OS between patients with versus without MRD negativity, it should be noted that their median follow-up times were relatively short (8.6 to 11 months).…”
Section: Promising Strategies To Achieve Mrd Negativity In High-risk Amlmentioning
confidence: 99%